Types of Hernia in Sulaimani Governorate - Saeed, Kamal Ahmed (Sulaimani Journal for Pure and Applied Sciences, 2005)
a retrospective study done to know the prevalence of abdominal wall hernia from the operations done druing the period of 1 septermber 1994 till the 30 deptermber 2000. Among 21222 patients eperated 4554 (21%) were hernias of different types . The mean age of the patients with abdominal wall hernias was around 46 years. Inguinal hernias appear to affect children and adolescents (0 -30) years more, while other types appear to affect middle ages (21-50) years more. Hernias where mostly of inguinal type, mainly unilateral on the right side, followed by umbilieal (and Para umbilieal), incisional, epigastric and femoral hernia.
Keywords: abdominal wall hernias; inguinal hernias; incisional hernias